Central Bank Digital Currency and banking choices - Jiaqi Li; Andrew Usher; Yu Zhu (Bank of Canada, 2024)
To what extent does a central bank digital currency (CBDC) compete with bank deposits? To answer this question, we develop and estimate a structural model where each household chooses which financial institution to deposit their digital money with. Households value the interest paid on digital money, the possibility of obtaining complementary financial products, and the access to in-branch services. A non-interest-bearing CBDC that does not provide complementary financial products can substantially crowd out bank deposits only if it provides an extensive service network. Imposing a large limit on CBDC holding would effectively mitigate this crowding out.
Keywords: E50; E58; 330; Central bank research; Digital currencies and fintech